A cryopreservation protocol for ex situ conservation of terrestrial orchids using asymbiotic primary and secondary (adventitious) protocorms - Bustam, B.; Dixon, Kingsley; Bunn, E. (Springer, 2016)
© 2015, The Society for In Vitro Biology. In a bid to better conserve endangered terrestrial orchids, we detail cryogenic research using a widely distributed terrestrial orchid, Caladenia latifolia, as a model species for development of cryopreservation for primary (seed generated) and secondary (adventitious) protocorms. Primary protocorm cryopreservation (using droplet vitrification) involved a number of experimental lines of inquiry: investigation of a suitable plant vitrification solution (PVS) by comparing three variants of a standard PVS (2, 3 and 4), determining the most suitable primary protocorm developmental stage for successful cryopreservation, testing the effectiveness of a preculture medium treatment prior to cryopreservation, and investigating temperature preconditioning at the preculture stage as well as different components of the recovery medium. Primary protocorms were generated using asymbiotic in vitro germination media developed by the authors specifically for the test species (half-strength MS macroelements and microelements with 5% (v/v) fresh filter sterilized coconut water). Secondary protocorms were propagated using an in vitro proliferation medium (½ MS with 5 µM a-naphthaleneacetic acid + 2 µM 6-benzylaminopurine). A modified preconditioning step was developed, involving incubation on ½ MS with 0.2 M raffinose for 48 h at 15°C instead of 20°C. The standard recovery medium (½ MS 1 µM zeatin + 0.5 µM gibberellic acid) was replaced after the first week following warming from liquid nitrogen (LN), with asymbiotic germination medium (½ MS + 5% (v/v) coconut water) for the remainder of the recovery phase. This new step increased the survival of primary protocorms from 68 to 85%. The average post-cryostorage regeneration of plants from primary protocorms increased from 17 to 48% after a 6-wk incubation. A similar protocol increased the survival of secondary protocorms from 63 to 84%. Regeneration of plants from secondary cryostored protocorms increased from 11 to 26% after 14 wk. The protocols developed here provide a useful template for advancing cryoconservation of other orchid taxa, particularly rare and threatened species.